2017
DOI: 10.1149/2.0731709jes
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Raman Spectroscopy of α- and γ-FeOOH during Cathodic Load

Abstract: Water reduction on corroded iron surfaces is technologically and fundamentally important. Here, the technological interest originates from the chlorate process where water reduction is the main cathodic process. Fundamentally, water reduction on oxide surfaces raises questions on the stability of the oxide and the nature of electrocatalytic surface sites. Two iron oxyhydroxides, αand γ-FeOOH, were electrodeposited on titanium substrate and their reduction processes were followed in detail with in-situ Raman sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 32 publications
3
35
0
Order By: Relevance
“…They are essentially identical to those reported in the literature for vivianite, the iron mineral Fe 3 (PO 4 ) 2 ⋅8 H 2 O that also occurs in various geological environments and in addition can be a breakdown product of iron oxyhydroxide minerals that interact with phosphate . The spectrum in Figure f was obtained from the yellowish orange precipitate presented in Figure d. The Raman bands at 271, 384, 580 cm −1 match the spectrum of goethite (α‐FeOOH) and are distinctly different from the spectrum of lepidocrocite (γ‐FeOOH) which has Raman peaks at 216, 250, 308 and 377 cm −1 . In the geological context, goethite and lepidocrocite are both common forms of ferric oxyhydroxide and found in soils, goethite being the more stable phase.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…They are essentially identical to those reported in the literature for vivianite, the iron mineral Fe 3 (PO 4 ) 2 ⋅8 H 2 O that also occurs in various geological environments and in addition can be a breakdown product of iron oxyhydroxide minerals that interact with phosphate . The spectrum in Figure f was obtained from the yellowish orange precipitate presented in Figure d. The Raman bands at 271, 384, 580 cm −1 match the spectrum of goethite (α‐FeOOH) and are distinctly different from the spectrum of lepidocrocite (γ‐FeOOH) which has Raman peaks at 216, 250, 308 and 377 cm −1 . In the geological context, goethite and lepidocrocite are both common forms of ferric oxyhydroxide and found in soils, goethite being the more stable phase.…”
Section: Resultssupporting
confidence: 80%
“…The chemical compositionso ft he precipitate membranes were probed by micro-Raman spectroscopy.F igure 2e shows the Ramans pectrum obtained from the porous precipitates in Figure 2b.I thasi ntense peaks in the low frequency range at 134, 211, and 277 cm À1 as well as broad bands at 387, 590, and 1003 cm À1 .T hey are essentially identicalt ot hose reportedi n the literature for vivianite, [21] the iron mineral Fe 3 (PO 4 ) 2 ·8 H 2 O that also occurs in variousg eological environments and in addition can be ab reakdown product of iron oxyhydroxide minerals that interact with phosphate. [22] The spectrum in Figure 2fwas obtained from the yellowish orange precipitate presented in Figure 2d.T he Ramanb ands at 271, 384, 580 cm À1 match the spectrum of goethite [23] (a-FeOOH)a nd are distinctly different from the spectrum of lepidocrocite [24] (g-FeOOH) which has Ramanp eaks at 216, 250, 308 and 377 cm À1 .I nt he geological context, goethite andl epidocrocite are both commonf ormso ff erric oxyhydroxide and found in soils, goethite being the more stable phase.…”
Section: Inorganic Precipitate Membranesmentioning
confidence: 93%
“…Additionally, there is an emergence of peak in O 1s XPS at 529.0 eV, which is corresponding to peroxo-like (O 2 2− ) species, and can be only observed after the OER test. [20,34] From Raman spectra ( Figure S22, Supporting Information), most characterized peaks of metal-nitride disappear, [10d,35] and three distinct peaks are observed that are corresponding to FeOOH [36] and CoOOH [3a,37] This result also confirms the phase transition on the surface of CoVFeN@NF in the OER process. In addition, the surface reconstruction and phase transition of the catalyst were further confirmed by the electrochemical test.…”
Section: Resultsmentioning
confidence: 73%
“…The HRTEM and SAED images demonstrate that the S‐FeOOH catalyst is polycrystalline with a phase of β‐FeOOH. The Raman spectra of S‐FeOOH (Figure S7, Supporting Information) presents several main peaks at 219, 248, 290, 396, 604, and 658 cm −1 , which are well ascribed to the characteristic peaks of FeOOH [ 42 ] and exhibit some Raman shifts compared with those of FeOOH due to the effect of S incorporation.…”
Section: Resultsmentioning
confidence: 99%